Comparing the efficacy of teaching cognitive, metacognitive and emotion regulation strategies on goal orientation of male students with low academic performance - hassan aslani; Marziyeh Alivandi Vafa; Amir panahali (مجله علوم روانشناختی, 2023)
Background: Considering the importance of academic performance during adolescence, one of the most important variables in this regard is Goal orientation. Based on the etiology of students' low academic performance, there are several interventions to be effective on psychological well-being; However, no study has investigated the impact of cognitive, metacognitive, and emotional regulation strategies on goal orietation. Aims: The present study was conducted with the aim of comparing the effectiveness of teaching cognitive, metacognitive and emotion regulation strategies on the goal orientation of male students with low academic performance in the second year of high school. Methods: This research was semi-experimental research with a pre-test-post-test design and a control group in terms of implementation. The statistical population consisted of all male students with low academic performance in the second year of high school in Tabriz city in 1400-1401. To select the research sample, 15 people were selected for each group in the form of purposeful sampling and randomly assigned to three experimental groups and one control group (60 people). The tools used in the research were the revised goal orientation questionnaire along with the implementation protocol of cognitive, metacognitive and emotion regulation strategies interventions. Results: Based on the results of multivariate covariance analysis, the effect of all three interventions of cognitive strategies, metacognitive strategies and emotion regulation on all goal orientation subscales was confirmed (p<0.05). Examining the effect size values showed that the interventions had the greatest effect on the objective component of avoidance circuit mastery with an effect size of 0.789 and then on the target component of tendency circuit mastery with an effect size of 0.763. The comparison of interventions showed that the effectiveness of metacognitive strategies intervention on goal orientation was significantly higher than the two interventions of cognitive strategies and emotion regulation (p<0.05). Conclusion: In general, it is concluded that educational interventions based on cognitive, metacognitive and emotion regulation strategies have the potential to be effective in improving the overall level of psychological well-being, and educational and therapeutic specialists can use these interventions to improve the level of academic performance of students.